Electroacupuncture-Induced Muscular Inflammatory Pain Relief Was Associated With Activation of Low-Threshold Mechanoreceptor Neurons and Inhibition of Wide Dynamic Range Neurons in Spinal Dorsal Horn - Duan-Mu, Cheng-Lin; Zhang, Xiao-Ning; Shi, Hong; Su, Yang-Shuai; Wan, Hong-Ye; Wang, Yi; Qu, Zheng-Yang; He, Wei; Wang, Xiao-Yu; Jing, Xiang-Hong (Frontiers in Neuroscience, 2021)
Acupuncture is an effective alternative therapy for pain management. Evidence suggests that acupuncture relieves pain by exciting somatic afferent nerve fibers to relieve pain. However, the mechanism about the interaction between neurons in different layers of spinal dorsal horn induced by electroacupuncture (EA) remains unclear. The aim of this study is to explore the mechanism of EA relieving inflammatory muscle pain by activating low threshold mechanoreceptor (LTM) neuron to inhibit spontaneous firing of wide dynamic range (WDR) neurons in spinal dorsal horn of the rats. Inflammatory muscle pain was produced by injecting complete Freund's adjuvant (CFA) into the right biceps femoris muscle. EA with intensity of threshold of A fibers (Ta) in ST34 considerably inhibited the abnormal spontaneous activities of electromyography (EMG) due to muscle inflammation, while EA with intensity of C fiber threshold (Tc) increased the abnormal activities of EMG. EA with Ta also ameliorated the imbalance of weight-bearing behavior. Microelectrode array with 750 μm depth of and 32 channels was used to record neuronal activities of WDR and LTM in different layers of the spinal dorsal horn. The spontaneous firing of LTM neurons were enhanced by EA-Ta, while the spontaneous firing of WDR neurons were inhibited. Moreover, EA-Ta led to a significant inverse correlation between the change rate of WDR and LTM neurons (r = - 0.64, P < 0.05). Taken together, the results indicated that EA could alleviate inflammatory muscle pain via activating the A-fiber afferent, which is mediated by increasing the LTM neurons and inhibiting the WDR neurons. This gave a promising evidence that EA-Ta will be applied to relieve muscular inflammatory pain in clinic.